Aquarium plants - Hiscock, Peter (Irvine, Calif. : BowTie, 2004)
The text addresses such vital topics as water quality, use of substrates, choosing healthy plants, and planting techniques, offering aquarists all the information they need to know to establish a well-planted, vibrant aquarium. In the chapter on lighting, the author has provided lists of plants that thrive in low, moderate, bright, and very bright light and explains the differing effects of light on plants. Aquarium Plants offers essential information on feeding plants, propagating plants, keeping plants healthy and choosing fish. Creative aquarists will welcome the sections on designing the aquarium, using various elements of display, and creating a themed tank (such as an African theme or a cold or hard water aquarium).
Keywords: Aquarium plants